The effects of teacher feedback on multiple-draft compositions in ESL classrooms - Othman, Shamshad Begham; Mohamad, Faizah (Faculty of Communication and Modern Languages, Universiti Utara Malaysia, 2007)
Teacher feedback plays a significant role in helping ESL learners acquire the writing skills. However, many research findings indicated that feedback on single draft essays does not help ESL learners much in improving the essays because these learners do not have the opportunity to revise, rewrite, and resubmit their work. Therefore, this study aims at examining the effects of teacher feedback on ESL learners’ compositions in terms of content, language and organization by instituting the multiple draft procedure. The participants of this study wrote a first draft; revised it after getting the feedback on content and further revised it after receiving feedback on language. The findings showed that there were significant mean differences in the content, language, organization and the total marks when the second and the third drafts were compared to the first draft.